ENCOReD: Meta-Analysis of Renal Denervation in 10 European Expert Centers - Mosely, Mary (MD Conference Express, 2013)
Renal denervation (RDN) is a novel treatment of resistant hypertension, based on the Renal Denervation in Patients with Uncontrolled Hypertension study [Symplicity HTN-2; Symplicity HTN-2 Investigators. Lancet 2010]. Yet, the magnitude and determinants of office and ambulatory blood pressure (BP) response to RDN have not been established. This article discusses the results of the first patient-level meta-analysis of the BP changes 6 months post RDN at 10 expert centers participating in the European Network Coordinating Research on Renal Denervation study [ENCOReD].